Physical, Psychosocial and Economic Wellbeing of Caregivers During COVID-19 Pandemic and its Impact on Developmental Milestones of Children (6 to < 30 Months): A Cross-Sectional Study - Shriya Sharma; Bhavna Langer; Koushal K Khajuria; Richa Mahajan; Rajiv K Gupta; Rashmi Kumari (Dr. Annil Mahajan, 2024)
Introduction: This study aimed to investigate the pattern of developmental milestones of children born during the COVID-19 pandemic and the impact of caregivers' physical, psychosocial and economic wellbeing on achievement of developmental milestones in children. Methodology: A cross-sectional study was conducted on children (6 to <30 months) born after March 2020 and their caregivers. Study tools included GAD-7, RBSK screening tool and pre-designed pre-tested semi structured questionnaire. Data was analysed using SPSS ver. 20.0. Results: Out of 228 children, developmental milestones were delayed in 62 (27.19%) children. In the age group of 12 to <15 months, the caregivers with GAD Score of >10 and <10, had 66.7% and 25% of their children with developmental delays and this difference was found to be statistically significant (p=0.04). Conclusion: An upward trend of developmental delays was observed in children born during pandemic although it was not affected by physical, psychosocial and economic wellbeing of care givers. Ironically, presence of caregivers and siblings at home for extended periods have also provided opportunities for care and interaction.